Plant Growth-Promoting Methylobacteria Selectively Increase the Biomass of Biotechnologically Relevant Microalgae - Krug, Lisa; Morauf, Christina; Donat, Christina; Müller, Henry; Cernava, Tomislav; Berg, Gabriele (Frontiers in Microbiology, 2020)
Microalgae, a diverse group of single-celled organisms exhibiting versatile traits, find broad applications in industry. However, high production costs require further efforts to optimize their production and to enhance biomass yields. In the present study, co-occurrence of algae and methylobacteria was observed when naturally occurring microalgae biofilms were subjected to 16S rRNA gene fragment amplicon sequencing. This bacterial group is so far less explored than other microalgae-associated bacteria in terms of mutualistic relationships that might be exploitable for biotechnological applications. In order to assess the potential of four plant growth-promoting strains from the genus Methylobacterium for increased algae biomass production, co-cultivation experiments were conducted with three industrially relevant microalgae (Chlorella vulgaris, Scenedesmus vacuolatus and Haematococcus lacustris). For S. vacuolatus and H. lacustris, a significant increase in algal biomass formation of 1.3-fold to up to 14-fold was observed after seven days of co-incubation. Visualization of mixed cultures using confocal laser scanning microscopy revealed a high abundance of methylobacteria in the phycosphere of H. lacustris and S. vacuolatus, visually attached to algae’s surface forming a biofilm-like assemblage. Genome analyses revealed that features attributable to enhanced algal growth include genes involved in the synthesis of vitamins, siderophores and plant hormones. Our results provide evidence for the constructability of novel symbiotic algae-bacteria relationships with inter-kingdom supportive capacities, underlining the potential of microbial consortia as promising tool for sustainable biotechnology and agriculture.